Respuesta :

Answer:

[tex]y = \frac{1}{2}x - 4[/tex]

Step-by-step explanation:

Given

[tex]y = \frac{1}{2}x[/tex]

Required

Shift [tex]3\ units[/tex] down and [tex]2\ units[/tex] right

[tex]y = \frac{1}{2}x[/tex]

Shift 3 units down

The rule is: (x,y)=> (x,y-a)

Where a is the number of units shifted down

In this case: [tex]a = 3[/tex]

So, we have:

[tex]y = \frac{1}{2}x[/tex] == > [tex]y = \frac{1}{2}x - 3[/tex]

Shift 2 units right

The rule is: (x,y)=>(x-b,y)

Where b is the number of units shifted right

In this case: [tex]b = 2[/tex]

So, we have:

[tex]y = \frac{1}{2}x - 3[/tex] ==> [tex]y = \frac{1}{2}(x - 2) - 3[/tex]

Open bracket:

[tex]y = \frac{1}{2}x - 1 - 3[/tex]

[tex]y = \frac{1}{2}x - 4[/tex]

Hence, the new equation after the transformation is:

[tex]y = \frac{1}{2}x - 4[/tex]